Evidence‐based practice among epilepsy specialist nurses in the Republic of Ireland: Findings from the SENsE study - Elliott, Naomi; Higgins, Agnes; Doherty, Colin (My University, 2019)
Aim: To describe how epilepsy specialist nurses in Ireland enact the evidence‐based practice dimension of their role. Background: The importance of epilepsy specialist nurses (ESNs) delivering evidence‐based care to people experiencing epilepsy is unquestionable, yet research into this aspect of the role is relatively sparse. Methods: A qualitative design was used, involving 12 epilepsy specialist nurses working in five units in Ireland, 24 multidisciplinary team members working with them and 35 people with epilepsy and their family members. Data were collected using individual and focus group interviews, observation and documentary analysis. Results: These ESNs were active in accumulating, translating, applying, generating and disseminating evidence. All were actively involved in, or leading audit and service evaluations, and used findings to improve practice. Their research activity mainly consisted of small‐scale unfunded research projects. Conclusions: These ESNs acted as opinion leaders and role models in relation to evidence‐based practice, including the generation of new knowledge through audit and research. Implications for Nursing Management: Organisations and managers need to support ESNs by ensuring that they have the necessary resources and competencies to accumulate, translate, apply, generate and disseminate relevant evidence. Future research should explore the impact of ESNs’ evidence‐based practice on patient outcomes.
PUBLISHED
http://dx.doi.org/10.1111/jonm.12747
Keywords: Advanced practitioner; Audit; Epilepsy specialist nurse; Evidence dissemination; Evidence-based practice; Epilepsy